2022
DOI: 10.1063/5.0078035
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanoparticle compression: Combining in situ TEM and atomistic modeling

Abstract: Platinum Nanoparticle Compression: Combining in situ TEM and Atomistic ModelingThe mechanical behavior of nanoparticles governs their performance and stability in many applications. However, the small sizes of technologically relevant nanoparticles, with diameters in the range of 10 nm or less, significantly complicate experimental examination.These small nanoparticles are difficult to manipulate onto commercial test platforms, and deform at loads that are below the typical noise floor of the testing instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In the end, this particle failed inhomogeneously and separated with part of the particle attached to the indenter. While the separation plane appears to be parallel to the indenter surface, our prior work on similar particles indicates failure along the expected Schmid-factor plane; therefore, we attribute the present shape to post-test flattening when the top portion of the particle slid off the lower portion and hit the substrate. The majority of the larger particles failed along an inclined plane, similar to those shown in Supporting Information Section S2.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the end, this particle failed inhomogeneously and separated with part of the particle attached to the indenter. While the separation plane appears to be parallel to the indenter surface, our prior work on similar particles indicates failure along the expected Schmid-factor plane; therefore, we attribute the present shape to post-test flattening when the top portion of the particle slid off the lower portion and hit the substrate. The majority of the larger particles failed along an inclined plane, similar to those shown in Supporting Information Section S2.…”
Section: Resultssupporting
confidence: 88%
“…This kink in the stress–strain curve and localized shearing (inhomogeneous deformation) is characteristic of displacive deformation, in which the deformation is carried primarily by dislocations. Prior investigations by others on nanowires , and earlier work on platinum and palladium nanoparticles have shown that defect plasticity in face-centered cubic (FCC) nanostructures proceeds via Shockley partial dislocations that leave behind stacking faults. However, the present testing was optimized for load measurement and the specific defects were not identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is also consistent with a previous measurement of an 11.5 nm platinum nanoparticle. 63 While the yield strength measurement is loading-direction-dependent, a simple calculation of all possible loading directions ( Section S2.2 in the Supporting Information) shows that the maximum Schmid factor varies little, with an average value of 0.462 and a standard deviation of 0.033. Therefore, the orientation of the particle is expected to have only a minor effect on measured yield strength.…”
Section: Resultsmentioning
confidence: 99%
“…[8] However, the study of the mechanical properties of NPs is much more complex. From an experimental point of view, in situ transmission electron microscopy [9][10][11][12][13][14] or scanning electron microscopy [15,16] nanoindentations have been developed for addressing this issue as they provide real-time monitoring of the deformation. Although powerful, these experimental techniques are applied to nanoparticles, which range in diameter from a few tens to several hundred nanometers and barely suitable for smaller ones.…”
Section: Introductionmentioning
confidence: 99%